The Study of Orphism - Torjussen, Stian Sundell (Nordlit, 2005)
In this article I shall provide a brief survey of the study of Orphism and give some indications of its present status. After a short introduction to the prior debate on the subject I will emphasize the role of the new material relevant to Orphism which has been unearthed and made available to scholars since the middle of the 1970s.